Foliar application of wood distillate boosts plant yield and nutritional parameters of chickpea. (29th June 2022) - Fedeli, Riccardo; Vannini, Andrea; Celletti, Silvia; Maresca, Viviana; Munzi, Silvana; Cruz, Cristina; Alexandrov, Dmitry; Guarnieri, Massimo; Loppi, Stefano
Abstract: In the quest for eco‐friendly products with biostimulant properties, foliar application of wood distillate (WD) was tested on the growth and yield of chickpea ( Cicer arietinum L.). WD (pyroligneous acid) is a by‐product of plant biomass pyrolysis and is rich in biologically active substances like polyphenols, alcohols, acids and esters. In this work, chickpea plants were sprayed weekly with 100 ml 0.25% (v/v) chestnut ( Castanea sativa Mill.) WD during the whole growing period, and at the end physiological and nutritional analyses were performed both on the whole plant and on seeds. While plant height and weight did not change significantly, seeds showed an increase in diameter (+11.2%) and weight (+33.3%), and in the content of starch (+45.9%), total soluble protein (+12.9%), total polyphenol (+16.4%) and antioxidant power (+28.4%). Overall, the content of essential free amino acids increased, except for lysine (−3.4%), phenylalanine (−10.5%) and methionine (−13.7%). Among all the mineral elements analysed, only potassium and magnesium decreased in WD‐treated plants, although values were within the common range for chickpea seeds. These results are a clear demonstration of the effectiveness of the use of WD on increasing the nutritional qualities of the edible parts of crop species, thus representing a possible solution to counteract human malnutrition and famine as well as environmental concerns. Abstract : Wood distillate sprayed on foliage of chickpea plants increases the content of most of the amino acids in the seeds, thus providing an effective and sustainable alternative to the consumption of animal‐based products for human nutrition.